Instruments that measure psychosocial factors related to vaccination: a scoping review protocol. Issue 12 (9th December 2019) - Kaufman, Jessica; Ryan, Rebecca; Betsch, Cornelia; Parkhill, Anne; Shapiro, Gilla; Leask, Julie; Menning, Lisa; Tugwell, Peter; Costa, Daniel SJ; Danchin, Margaret; Rada, Gabriel; Hill, Sophie
Abstract : Introduction: As vaccine-preventable disease outbreaks increase, there is growing international interest in monitoring public attitudes towards vaccination and implementing and evaluating vaccine promotion interventions. Outcome selection and measurement are central to intervention evaluation. Measuring uptake rates alone cannot determine which elements in a multicomponent vaccine-promotion intervention are most effective, why specific populations are undervaccinated or when confidence in vaccines is wavering. To develop targeted and cost-effective interventions and policies, it is necessary to measure vaccination-related psychosocial factors such as knowledge, attitudes and aspects of decision-making. This scoping review aims to identify, compare and summarise the properties and validation of instruments for measuring vaccination-related psychosocial factors and identify gaps where no instruments exist. Methods and analysis: We will search Medline OVID, Embase OVID, CINAHL and PsycINFO with no date restriction, using a pilot-tested search strategy of terms related to vaccination: knowledge, attitudes, trust, acceptance and decision-making and measurement, psychometric testing or validation. This search will be supplemented with manual search and expert consultation. We will include studies that describe instrument development, adaptation or testing and include evaluation of at least two measurement properties (eg, content, criterion, or construct validity; test–retest reliability; internal consistency; sensitivity; responsiveness). Instruments measuring a vaccination-related psychosocial factor in any population will be included. All studies will be screened by one reviewer, with a sample double-screened to confirm accuracy. Disagreements will be resolved with a third reviewer. Data will be synthesised narratively and through summary tables to chart and compare instrument characteristics such as factors measured, date and/or location of development or validation, measurement properties evaluated and population. Ethics and dissemination: This scoping review aims to provide an overview of existing instruments and ascertain measurement gaps where no measurement instruments currently exist. The identified instruments will form the basis of an open-access online repository of instruments.